A survey of turfgrass irrigation water quality in Pennsylvania. Issue 1 (4th April 2022) - Landschoot, Peter James; Spargo, John; McGraw, Benjamin A.
Abstract: Surveys of irrigation water reveal important information about water quality in different geographic regions and can serve as a reference to compare with individual samples submitted to labs. This survey aimed to establish a baseline profile of turfgrass irrigation water quality from nonamended and noneffluent sources in Pennsylvania that can be compared with water quality data from other geographic regions and future surveys in the Mid‐Atlantic region, and to improve test report guidelines for samples submitted to labs. The survey was conducted between fall 2007 and spring 2019 and included 190 irrigation water samples. Samples were analyzed at Penn State's Agricultural Analytical Services Laboratory (PSAASL) for pH, alkalinity, hardness, electrical conductivity, total dissolved solids, sodium absorption ratio, bicarbonate, carbonate, residual sodium carbonate, nitrate‐N, ammonium‐N, and 13 elements. The results showed acceptable irrigation water quality according to published guidelines, with some exceptions, which included high (and potentially problematic) values for sodium, total dissolved solids, and sulfur, but these represented ≤10% of the samples. According to the results, most normal ranges and upper limits for the quality parameters of turfgrass irrigation water should be similar to those currently listed in PSAASL reports. However, the normal ranges for pH, alkalinity, and bicarbonate should be expanded to account for the numerous water samples (> 45%) that exceeded the maximum range listed in test reports. The normal range and upper limit of nitrate‐N should be lowered in PSAASL reports to reflect the results and concerns about environmental and health‐related effects. Core Ideas: Baseline water quality data are needed for turfgrass irrigation guidelines in Pennsylvania. The survey indicated that normal ranges for pH, alkalinity, and bicarbonate should be widened. The normal range and upper limit of nitrate‐N should be decreased in irrigation water reports. Turfgrass irrigation water in Pennsylvania is of high quality, with minor exceptions.